(untitled) (ResearchJet Journal of Analysis and Inventions, 2022)
Polymer composite materials were manufactured The base material was made of low-density polyethylene using the thermal fusion method and supported using CuSO4 powder, which is in the Nano-form and in volumetric ratios by adding (5,10,15,20,25), the manufactured models were thermally treated for three periods (3,6,9) and at temperatures (40,60,80). The models were subjected to a set of mechanical tests that include (shear stress, compressive strength), X-ray diffraction (XRD) and scanning electron microscopy (SEM) examinations. Mechanical properties, where a state of filling the voids occurs regularly and effectively, and this percentage was within the 15%, in addition to the temperature, which played a major role in improving some of the polymeric properties shown by the mechanical properties of the manufactured composite material.